Pengaruh Employee Enrichment, Employee Safety, Employee Commitment terhadap Employee Performance di Moderasi oleh Psychological Well-Being pada CV. Jaya Abadi Beton - Widiana, Dinar; Sirine, Hani (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of each variable of employee enrichment, employee safety, employee commitment on employee performance in moderation of psychological well-being. The research method used is a quantitative approach with an explanatory type. The population that became the subject of the study were all employees of CV. Jaya Abadi Beton, totaling 158 people with a sample of 100 people. The results of this study are employee enrichment has an effect on employee performance, employee safety has an effect on employee performance, employee commitment has an effect on employee performance, psychological well-being has not been able to moderate the effect of employee enrichment on employee performance, employee safety has an effect on employee performance that can be moderated by psychological well-being, employee commitment has an effect on employee performance that can be moderated by psychological well-being.